Sistem Pendukung Keputusan Rekomendasi Wedding Organizer Terbaik Menerapkan Metode MOORA dan Pembobotan ROC - Muhammad Naufal Rifqi; Agus Iskandar (Journal of Information System Research (JOSH), 2023)
Wedding Organizer provides a variety of services to help couples prepare and organize their wedding according to their wishes. However, with so many choices of wedding planners in Medan, couples often have difficulty choosing the best one for their needs. Decision Support System (DSS) is a strategy that assists in decision making by applying mathematical and statistical techniques to available data. In the case of selecting a Wedding Organizer, SPK can be used to assist couples in assessing and choosing the optimal option that matches the parameters that have been set. This complex selection process involves careful consideration of price, quality of service, reputation, portfolio and experience. The MOORA method with the ROC weighting method is one of the methods that can be used in DSS to select the best alternative based on several criteria. The MOORA method allows ranking alternatives based on different criteria, while the ROC method weighting can help overcome data imbalance problems and optimize model performance in decision making. From the results of calculations using the MOORA and ROC methods that have been carried out from 8 alternatives, it produces recommendations for the wedding organizer, namely getting 4 highly recommended alternatives while 4 other alternatives are sufficiently recommended. The research findings show that the application of the MOORA method with the ROC Method assessment is able to provide recommendations that are more precise and in accordance with the established criteria, assisting couples in making accurate and efficient decisions when choosing the Wedding Organizer that best suits their wishes and needs.